(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Diabetes mellitus has been a key degenerative disease affecting the world’s population. Lycopersicon esculentum (Tomato), a fruit consumed by many and known to have certain phytochemicals was used to determine its hypoglycemic effect on alloxan induced diabetic rats. The tomato was dried, pulverized and dissolved in distilled water and administered orally to albino rats in various concentrations according to their body weight. 30 albino rats were divided into 6 groups of 5 rats each. Groups I and II served as normal and diabetic control respectively, while groups III to VI were induced with diabetes and treated with different concentrations of the prepared tomato. After 14 days of treatment with various concentrations of tomato, there was a marked decrease in blood sugar levels at all the study concentrations. The result of the lipid profile a significant increase (p<0.05) in total cholesterol (150.67±7.02 mg/dL), triglyceride (159.33±5.03 mg/dL), LDL-Cholesterol (77.53±1.83 mg/dL) and a decrease in HCL-Cholesterol (51.67±1.00 mg/dL) levels in untreated diabetic rats when compared to the normal control. Upon treatment with 200 mg/kg of tomato, there was a significant decrease (p< 0.05) in the levels of Triglyceride, total cholesterol and LDL-cholesterol and an increase in the HDL-cholesterol. These results suggest that tomato may have the ability to reduce blood sugar level and the risk of cardiovascular disease.